METHODS OF INCREASING THE DURABILITY OF WOODWORKING TOOLS: https://doi.org/10.5281/zenodo.14917425 - Boltakov , Sirojiddin; Tolliboev , Azizbek (Journal of Contemporary World Studies, 2025)
This article analyzes the methods of increasing the durability of woodworking tools. The factors affecting the wear of the tools, the technological processes used to extend their service life, the importance of solid alloys and protective coatings are highlighted. Recommendations are also made to improve the durability of woodworking tools through heat treatment, sharpening and other effective methods. This research is aimed at improving the efficiency of the woodworking process and reducing the cost of production.